Combined Influence of LDLR and HMGCR Sequence Variation on Lipid-Lowering Response to Simvastatin - Lara M. Mangravite; Marisa W. Medina; Jinrui Cui; Sheila Pressman; Joshua D. Smith; Mark J. Rieder; Xiuqing Guo; Deborah A. Nickerson; Jerome I. Rotter; Ronald M. Krauss (2010)
Although statins are efficacious for lowering low-density lipoprotein cholesterol, there is wide interindividual variation in response. We tested the extent to which combined effects of common alleles of LDLR and HMGCR can contribute to this variability.Haplotypes in the LDLR 3'-untranslated region (3-UTR) were tested for association with lipid-lowering response to simvastatin treatment in the Cholesterol and Pharmacogenetics trial (335 blacks and 609 whites). LDLR haplotype 5 (LDLR L5) was associated with smaller simvastatin-induced reductions in low-density lipoprotein cholesterol, total cholesterol, non-high-density lipoprotein cholesterol, and apolipoprotein B (P=0.0002 to 0.03) in blacks but not whites. The combined presence of LDLR L5 and previously described HMGCR haplotypes in blacks was associated with significantly attenuated apolipoprotein B reduction (-22.4+/-1.5%, N=89) compared with both noncarriers (-30.6+/-1.5%, N=78, P=0.0001) and carriers of either individual haplotype (-28.2+/-1.1%, N=158, P=0.001). We observed similar differences when measuring simvastatin-mediated induction of low-density lipoprotein receptor surface expression using lymphoblast cell lines (P=0.03).We have identified a common LDLR 3-UTR haplotype that is associated with attenuated lipid-lowering response to simvastatin treatment. Response was further reduced in individuals with both LDLR and previously described HMGCR haplotypes. Previously identified racial differences in statin efficacy were partially explained by the greater prevalence of these combined haplotypes in blacks.